Teachers’ Participation in the Guidance Services in Elementary Multigrade Schools - Suayan-Bondad, Crisha Belle (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined teachers’ participation in guidance services in elementary multigrade schools, focusing on the implementation of guidance programs, the extent of teacher involvement, and the challenges encountered. Anchored on the Comprehensive School Counseling Model of the American School Counselor Association (ASCA), the study adopted a sequential exploratory mixed methods design. Qualitative data were collected through unstructured interviews and open-ended questionnaires with multigrade teachers, followed by a quantitative phase using structured survey instruments administered to 30 teachers, 50 learners, and 20 school heads or teachers-in-charge in the District of Bokod, Benguet. Thematic analysis and descriptive statistics were employed to analyze the data. Findings revealed that foundational guidance services such as inventory, referral, testing, and information dissemination were widely implemented, while transitional services were moderately practiced and specialized services—particularly counseling, evaluation, and research—were least implemented. Teachers demonstrated a frequent level of participation overall, particularly in tasks aligned with instructional roles such as data gathering and learner support, but showed lower engagement in specialized functions requiring technical expertise. Major challenges included heavy workload, lack of training, insufficient resources, limited time, and weak parental involvement, resulting in fragmented service delivery. Teachers relied on coping mechanisms such as integrating guidance into instruction, collaboration with peers and external agencies, and personal adaptive strategies. The study concludes that while teachers play a critical role in sustaining guidance services, systemic constraints limit the depth and consistency of implementation. It recommends capacity-building, institutional support, structured programs, and strengthened partnerships to enhance service delivery. The study aligns with SDG 3 (Good Health and Well-Being) and SDG 4 (Quality Education) by highlighting the role of guidance services in promoting learners’ mental health and inclusive education. It contributes to sustainability by supporting institutional strengthening, improving psychosocial support systems, and fostering equitable and holistic learner development in resource-constrained educational contexts.
Keywords: Counseling Services; Guidance Services; Multigrade Schools; Teacher Participation; Educational Challenges; Psychosocial Support; School Counseling; Sustainable Education